1987
DOI: 10.1042/bj2480069
|View full text |Cite
|
Sign up to set email alerts
|

Basement-membrane heparan sulphate with high affinity for antithrombin synthesized by normal and transformed mouse mammary epithelial cells

Abstract: Basement-membrane proteoglycans, biosynthetically labelled with [35S]sulphate, were isolated from normal and transformed mouse mammary epithelial cells. Proteoglycans synthesized by normal cells contained mainly heparan sulphate and, in addition, small amounts of chondroitin sulphate chains, whereas transformed cells synthesized a relatively higher proportion of chondroitin sulphate. Polysaccharide chains from transformed cells were of lower average Mr and of lower anionic charge density compared with chains i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…A mutation in the appropriate EXT protein might affect such interaction as well as the initial polymerization reaction itself, with presently unpredictable effects on the structure of the final product. Indeed, many different types of tumors are associated with distinct changes in glycosaminoglycan, particularly HS, structure (23)(24)(25)(26)(27). Although the mechanisms behind these changes are generally unknown, the alterations may be expected to affect functional interactions with a variety of proteins that are potentially involved in neoplastic transformation.…”
Section: Cloning Of Heparan Sulfate Polymerase 26266mentioning
confidence: 99%
“…A mutation in the appropriate EXT protein might affect such interaction as well as the initial polymerization reaction itself, with presently unpredictable effects on the structure of the final product. Indeed, many different types of tumors are associated with distinct changes in glycosaminoglycan, particularly HS, structure (23)(24)(25)(26)(27). Although the mechanisms behind these changes are generally unknown, the alterations may be expected to affect functional interactions with a variety of proteins that are potentially involved in neoplastic transformation.…”
Section: Cloning Of Heparan Sulfate Polymerase 26266mentioning
confidence: 99%
“…7 Furthermore, 3-OST-2 should sulfate the sequence containing GlcA2S with much higher efficiency because the population of a sulfated glucuronic acid is approximately 5-50-fold less frequent than that of a sulfated iduronic acid in any given heparan sulfate (35)(36)(37)(38). Our Northern analysis has demonstrated that 3-OST-2 is predominantly expressed in human brain as described in the accompanying article (24).…”
Section: -O-sulfation Of Heparan Sulfatementioning
confidence: 99%
“…The HS-GAGs show distinct alterations in sulfation patterns, total chain length, and the number of sulfated domains. A number of earlier studies have indicated malignancy-associated undersulfation of cell surface HS (43)(44)(45). Recent detailed structural analysis has revealed the specific structural changes of HS isolated from human adenoma and carcinoma cells during the colon carcinogenesis (46).…”
Section: Table III Effects Of Gags On the Collagen-induced Cord Formamentioning
confidence: 99%